2005
DOI: 10.1128/ec.4.7.1211-1220.2005
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of an Evolutionarily Distinct Phosphopantetheinyl Transferase in the Apicomplexan Cryptosporidium parvum

Abstract: Recently, two types of fatty acid synthases (FASs) have been discovered from apicomplexan parasites. Although significant progress has been made in characterizing these apicomplexan FASs, virtually nothing was previously known about the activation and regulation of these enzymes. In this study, we report the discovery and characterization of two distinct types of phosphopantetheinyl transferase (PPTase) that are responsible for synthesizing holo-acyl carrier protein (ACP) from three apicomplexan parasites: sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 47 publications
(65 reference statements)
1
29
0
Order By: Relevance
“…The level of CpACBP1 transcripts was relatively low during early intracellular development (from 3 to 24 h post-infection), but gradually increased with the time of infection. This expression pattern differs from that of many other C. parvum genes, such as the replication protein A subunits, CpSFP-PPT and b-tubulin, but is similar to those of oocyst wall proteins in this parasite (Abrahamsen & Schroeder, 1999;Cai et al, 2005;Millership et al, 2004a;Rider et al, 2005). Such a differential expression pattern is also supported by Western blot and immunofluorescence microscopic analyses that only detected CpACBP1 protein in the intracellular parasites, but not in oocysts or free sporozoites (Figs 8 and 9).…”
Section: Cpacbp1 Has Highest Binding Affinity To C16 : 0 Palmitoyl-coasupporting
confidence: 53%
“…The level of CpACBP1 transcripts was relatively low during early intracellular development (from 3 to 24 h post-infection), but gradually increased with the time of infection. This expression pattern differs from that of many other C. parvum genes, such as the replication protein A subunits, CpSFP-PPT and b-tubulin, but is similar to those of oocyst wall proteins in this parasite (Abrahamsen & Schroeder, 1999;Cai et al, 2005;Millership et al, 2004a;Rider et al, 2005). Such a differential expression pattern is also supported by Western blot and immunofluorescence microscopic analyses that only detected CpACBP1 protein in the intracellular parasites, but not in oocysts or free sporozoites (Figs 8 and 9).…”
Section: Cpacbp1 Has Highest Binding Affinity To C16 : 0 Palmitoyl-coasupporting
confidence: 53%
“…It appears that all of these ACP domains need to be activated by the addition of a prosthetic phosphopantetheinyl moiety, which is catalyzed by PPT. Cryptosporidium possesses one single SFP-type PPT (CpSFP-PPT) that was able to activate the ACP domains in CpFAS1 (Cai et al, 2005). Here we have shown that CpSFP-PPT was able to activate the ACP domain in CpPKS1 (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…Because recombinant ACP domains from CpFAS1 could only be expressed in the inactive apo form Cai et al, 2005), we suspected that the bacterial host cells were also unable to phosphopantetheinylate the ACP domain in the CpPKS1 loading unit. Therefore, we wanted to test the ability of recombinant C. parvum SFP-type phosphopantetheinyl transferase (CpSFP-PPT) to activate the apo-ACP domain of the CpPKS1 loading unit.…”
Section: Phosphopantetheinylation Of the Acp Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…To amplify C. parvum 18S rRNA as a control for normalization, we used the previously reported primers 995F (5Ј TAG AGA TTG GAG GTT GTT CCT 3Ј) and 1206R (5Ј CTC CAC CAA CTA AGA ACG GCC 3Ј) (1). The relative level of CpLCE1 transcripts was expressed relative to that of 18S rRNA, and values are reported based on at least three replicates as previously described (5,28).…”
Section: Methodsmentioning
confidence: 99%